2020
DOI: 10.1111/iej.13258
|View full text |Cite
|
Sign up to set email alerts
|

Immediate clinical and microbiological evaluation of the effectiveness of 0.5% versus 3% sodium hypochlorite in root canal treatment: A quasi‐randomized controlled trial

Abstract: Ulin C, Magunacelaya-Barria M, Dahl en G, Kvist T.Immediate clinical and microbiological evaluation of the effectiveness of 0.5% versus 3% sodium hypochlorite in root canal treatment: A quasi-randomized controlled trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 38 publications
1
24
0
1
Order By: Relevance
“…The results agree with other studies where the effectiveness of NaOCl as antimicrobial agent has been demonstrated [24][25][26][27][28][29][30][31]. The alkaline pH of NaOCl induces biosynthetic alterations in cell metabolism, protein denaturation, enzymatic inhibition, and destruction of phospholipids, [32] intervening in the integrity of the cytoplasmic membrane, which grants its bactericidal effect and tissue dissolution, for that reason, it is the chemical agent most used during endodontic therapy [33,34]. Nevertheless, being a non-selective disinfectant agent, NaOCl, can lead to cellular alterations such as chromosomal aberration, frequency of micronuclei, necrotic or apoptotic cells, and binucleated cells [35].…”
Section: Discussionsupporting
confidence: 88%
“…The results agree with other studies where the effectiveness of NaOCl as antimicrobial agent has been demonstrated [24][25][26][27][28][29][30][31]. The alkaline pH of NaOCl induces biosynthetic alterations in cell metabolism, protein denaturation, enzymatic inhibition, and destruction of phospholipids, [32] intervening in the integrity of the cytoplasmic membrane, which grants its bactericidal effect and tissue dissolution, for that reason, it is the chemical agent most used during endodontic therapy [33,34]. Nevertheless, being a non-selective disinfectant agent, NaOCl, can lead to cellular alterations such as chromosomal aberration, frequency of micronuclei, necrotic or apoptotic cells, and binucleated cells [35].…”
Section: Discussionsupporting
confidence: 88%
“…However, the effects are restricted to the main root canal, and instruments usually fail to touch all the walls, causing unprepared areas to harbor microorganisms (3). In addition to that, studies have revealed that chemomechanical preparation using NaOCl at different concentrations is not able to render root canals free of bacteria, and 40% to 60% of the root canals are still positive for bacterial presence (1,4).…”
Section: Introductionmentioning
confidence: 99%
“…Also, despite sodium hypochlorite (NaOCl) being the chemical substance used in all studies, its concentration ranged from 1% to 5%. It has been shown that the concentration of NaOCl does not appear to influence the reduction of the microbial load of the root canal system [ 61 62 ], but the volume of irrigant solution, the frequency of irrigant renewal, and the time that it remains inside the root canal are factors that play an essential role during treatment [ 63 64 ]. However, the included studies did not describe these aspects.…”
Section: Discussionmentioning
confidence: 99%